Investigation of the cytotoxicity induced by cannabinoids on human ovarian carcinoma cells - Kartheek Sooda; Simon J. Allison; Farideh A. Javid (Wiley, 2023)
Abstract Cannabinoids have been shown to induce anti‐tumor activity in a variety of carcinoma cells such as breast, prostate, and brain. The aim of the present study is to investigate the anti‐tumor activity of cannabinoids, CBD (cannbidiol), and CBG (cannabigerol) in ovarian carcinoma cells sensitive and resistant to chemotherapeutic drugs. Sensitive A2780 cells and resistant A2780/CP70 carcinoma cells and non‐carcinoma cells were exposed to varying concentrations of CBD, CBG, carboplatin or CB1 and CB2 receptor antagonists, AM251 and AM630, respectively, alone or in combination, at different exposure times and cytotoxicity was measured by MTT assay. The mechanism of action of CBD and CB in inducing cytotoxicity was investigated involving a variety of apoptotic and cell cycle assays. Treatment with CBD and CBG selectively, dose and time dependently reduced cell viability and induced apoptosis. The effect of CBD was stronger than CBG in all cell lines tested. Both CBD and CBG induced stronger cytotoxicity than afforded by carboplatin in resistant cells. The cytotoxicity induced by CBD was not CB1 or CB2 receptor dependent in both carcinoma cells, however, CBG‐induced cytotoxicity may involve CB1 receptor activity in cisplatin‐resistant carcinoma cells. A synergistic effect was observed when cannabinoids at sublethal doses were combined with carboplatin in both carcinoma cells. The apoptotic event may involve loss of mitochondrial membrane potential, Annexin V, caspase 3/7, ROS activities, and cell cycle arrest. Further studies are required to investigate whether these results are translatable in the clinic. Combination therapies with conventional cancer treatments using cannabinoids are suggested.